Gobiernos reformistas en Uruguay 1947-1958: ¿profundización de la democracia en los inicios de la Guerra Fría? - Cecilia Arias (Centre de Recherches sur les Mondes Américains, 2018)
The purpose of this paper is to analyze the political formulation and the social and cultural effects of the uruguayan reformist governments in the early years of the Cold War (1947-1958), focusing on the concept of democracy that they defended, the measures they promoted and the consequences of their actions.These governments developed a nationalist, industrialist, pro-agricultural and redistributivist model. The speeches and actions of the reformist political cast were inscribed in a concept of democracy in which freedom and social justice were prioritized, including economic, social and cultural rights, as well as political and civil rights. They pointed to a deepening of democracy from a reformist liberal ideological perspective.They differed from other reformist projects in the region, identified as populisms, in the emphasis they put on democratic freedoms while sharing some of their characteristics.They acted during a phase of economic growth of the country that ceased in 1957; year in which a deep crisis begins that highlights the weaknesses of the model and its failure, which led to the triumph of the opposition forces in the 1958 elections.